2015
DOI: 10.1080/21655979.2015.1030543
|View full text |Cite
|
Sign up to set email alerts
|

Alginate lyase: Review of major sources and classification, properties, structure-function analysis and applications

Abstract: A lginate lyases catalyze the degradation of alginate, a complex copolymer of a-L-guluronate and its C5 epimer b-D-mannuronate. The enzymes have been isolated from various kinds of organisms with different substrate specificities, including algae, marine mollusks, marine and terrestrial bacteria, and some viruses and fungi. With the progress of structural biology, many kinds of alginate lyases of different polysaccharide lyases families have been characterized by obtaining crystal structures, and the catalytic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
177
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 237 publications
(182 citation statements)
references
References 63 publications
2
177
0
3
Order By: Relevance
“…As shown in Figure 4, PL7 alginate lyases contain three highly conserved amino acid sequences, (S/T/N)EL, Q(I/V)H, and YFKAG(V/I)YNQ, which were thought to play an important role in catalytic activity or the folding of the structure [27]. Researches revealed that enzymes containing QIH or QVH in the conserved region had substrate specificity of G-block and M-block, respectively [28].…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Figure 4, PL7 alginate lyases contain three highly conserved amino acid sequences, (S/T/N)EL, Q(I/V)H, and YFKAG(V/I)YNQ, which were thought to play an important role in catalytic activity or the folding of the structure [27]. Researches revealed that enzymes containing QIH or QVH in the conserved region had substrate specificity of G-block and M-block, respectively [28].…”
Section: Discussionmentioning
confidence: 99%
“…Lentivector suspension containing 6 Â 10 4 TU were incubated within treated media, and following times of 10, 30, and 60 minutes, the lentivector suspension was diluted with DMEMc and applied to HEK-293T cells. Alternatively, 7.5 Â 10 4 TU of lentivectors were encapsulated within alginate microgels, released by hydrogel enzymatic digestion with alginate lyase 53 (Sigma Aldrich), and then applied to HEK-293T cells. For all experiments the transduction efficiency of the lentivectors was quantified by flow cytometry (410 000 events analyzed).…”
Section: Effect Of Ph and Encapsulation On Lentivector Functionalitymentioning
confidence: 99%
“…At selected time points spanning 10 days, the supernatant was collected and stored at À20 1C (until sample concentration was determined), and a fresh aliquot of medium was added over each disk. Alternatively, lentivectors were immediately recovered from a separate 12 mL of microgels by digestion with 10 units per mL of alginate lyase 53 (n = 3). The concentrations of lentivectors in supernatant and digestion samples were determined in terms of the p24 capsid protein.…”
Section: Quantification Of Lentivector Release From Alginate Microgelsmentioning
confidence: 99%
“…Most of the elucidated enzymes are endo-type lyases that internally and randomly degrade alginate, producing a series of unsaturated oligosaccharides with different degrees of polymerization (19,22,23). Only a few of these enzymes have been reported as exo-type enzymes that gradually cut the polysaccharide, yielding predominantly monosaccharides as products (24)(25)(26)(27)(28)(29).…”
mentioning
confidence: 99%
“…Moreover, the enzymatic degradation of bacterial alginate using alginate lyases may assist antibiotics in killing Pseudomonas pathogens or may facilitate more efficient inhibition of bacterial growth (16-18). Hence, alginate lyases are potential enzyme tools for the clinical treatment of human cystic fibrosis syndrome.During the last decade, nearly 100 alginate lyases have been discovered in ocean animals, bacteria, and bacterial phages (10,11,(19)(20)(21). Most of the elucidated enzymes are endo-type lyases that internally and randomly degrade alginate, producing a series of unsaturated oligosaccharides with different degrees of polymerization (19,22,23).…”
mentioning
confidence: 99%